2017
DOI: 10.1007/s00246-017-1718-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Levosimendan in Postoperative Setting After Surgical Repair of Congenital Heart Disease in Children

Abstract: Low cardiac output is one of the most common complications after cardiac surgery. Levosimendan, a new inotrope agent, has been demonstrated in adult patient to be an effective treatment for this purpose when classical therapy is not effective. The aim of this study was to evaluate the effect of Levosimendan on cardiac output parameters in cardiac children with low cardiac output syndrome (LCOS.). We carried out a retrospective analysis on 62 children hospitalized in our pediatric intensive care unit (PICU) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Anesthesiologists in our center have adopted the mindset that levosimendan should be administered at the discretion of the clinician as early as possible, and generally be started at the induction of anesthesia to decrease the incidence of postoperative LCOS and to prevent any unwanted consequences. The retrospective but single-group analysis conducted by Amiet et al ( 15 ) involving 62 pediatric patients in the ICU after cardiac surgery demonstrated that using levosimendan as a rescue treatment once LCOS occurred could increase central venous oxygen saturation and reduce lactate 24 h later. They reported that in their clinical routine, they even infused the drug 24 h before various complicated surgeries in newborns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anesthesiologists in our center have adopted the mindset that levosimendan should be administered at the discretion of the clinician as early as possible, and generally be started at the induction of anesthesia to decrease the incidence of postoperative LCOS and to prevent any unwanted consequences. The retrospective but single-group analysis conducted by Amiet et al ( 15 ) involving 62 pediatric patients in the ICU after cardiac surgery demonstrated that using levosimendan as a rescue treatment once LCOS occurred could increase central venous oxygen saturation and reduce lactate 24 h later. They reported that in their clinical routine, they even infused the drug 24 h before various complicated surgeries in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that in their clinical routine, they even infused the drug 24 h before various complicated surgeries in newborns. On other occasions, levosimendan was only regarded as a Supplementary agent during CPB weaning ( 16 18 ) or even as a rescue when difficulty arose ( 15 ). The LEVO-CTS ( 10 ) trial even claimed that levosimendan administration started just before surgery was actually not effective enough to reduce or avoid cardiac damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Amiet et al also studied Levosimendan in pediatric patients and observed lower lactate levels. [33] Study by Matthias et al (55) also showed better metabolic effects of milrinone in comparison to adrenaline in term of lower lactate level in plasma. [34] Tatlis et al also suggested that Milrinone has a beneficiary effect on aerobic tissue metabolism after extracorporeal circulation reflected on serum lactate, possibly due to a combination of positive inotropic and peripheral vasodilatory effect of the drug.…”
Section: Vyas Et Al: Hemodynamic Effects Of Levosimendan and Milrinonementioning
confidence: 99%
“…1 This is an important area of research, as lowcardiac-output syndrome (LCOS) after congenital heart surgery occurs in up to 25% of pediatric patients and is a major contributor to postoperative morbidity and mortality. 2 Milrinone, a phosphodiesterase-3 inhibitor, long has been used as an inodilator to prevent or attenuate the development of LCOS after cardiac surgery.…”
mentioning
confidence: 99%